PENDIDIKAN KARAKTER BERBASIS KEBUDAYAAN LOKAL: ANALISIS NILAI MULTIKULTURALISME DALAM TRADISI RAMBU SOLO’ DI TORAJA - Gita Lorensia Dannari (Al-Fikru : Jurnal Pendidikan Dan Sains, 2021)
in the current era of globalization, the world community can easily relate to each other and interact, so that in everyday life humans are always in contact with a multicultural society. This is also experienced by the people of Indonesia as a very diverse country. This shows that it is necessary to inculcate multicultural values, especially for the younger generation of Indonesia, so that they always show a way of life that is mutually respectful, sincere, tolerant and cooperative towards the cultural diversity that lives in the midst of a society with a high level of plurality. These values of multiculturalism can be explored in local traditions or cultures from every region in Indonesia. One of them is the ‘Rambu Solo’ tradition which is very closely related to the life of the Toraja people, through this tradition the younger generation is taught to always respect each other, help each other, trust each other and other important values. Therefore, through literature research methods and direct experience, the author will conduct a study of the multicultural values contained in the Rambu Solo' tradition in Toraja..Keywords: Multiculturalism, Rambu Solo', Toraja